PERBANDINGAN JUMLAH KASUS POSTDURAL PUNCTURE HEADACHE PADA PASIEN PASCA SECTIO CAESAREA DENGAN ANESTESI SPINAL MENGGUNAKAN JARUM TIPE QUINCKE 25G DAN 26G DI RSUD ARIFIN ACHMAD - Randa Pratama; R. Sutantri EP; Siti Mona Amelia.L (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Postdural Puncture Headache (PDPH) is an iatrogeniccomplication from spinal anesthesia caused by puncture or laceration fromduramater which leads to leakage of cerebrospinal liquor (LCS). Manyfactors to influence the incidence of PDPH one of which is the size ofspinal needle. The purpose of this research to know comparison theincidence of PDPH between Quincke 25G and 26G in patients with postsectio caesarea. In this cohort analytic study, 68 consecutive patients withpost sectio caesarea under spinal anaesthesia accordance to the inclusiveand exlusive criteria were included. Incidence of PDPH in the Quincke25G needle is 4 repondents (11,8%) and the 26G Quincke is 2 respondents(5.9%). With the most common sites of pain on Frontooccipital, andseverity were assessed using the Visual Analogue Scale (VAS). The resultsof this research showed that no significant relationship between the size ofthe spinal needle with the incidence of PDPH in sectio caesarea patient atthe Arifin Achmad Hospital.Keyword : Post Dural Puncture Headache, PDPH, Comparison TheIncidence of PDPH, Quincke 25G, Quincke 26G, Spinalanaesthesia